2015
DOI: 10.18632/oncotarget.5363
|View full text |Cite
|
Sign up to set email alerts
|

The novel HSP90 inhibitor AT13387 potentiates radiation effects in squamous cell carcinoma and adenocarcinoma cells

Abstract: Overexpression of heat shock protein 90 (HSP90) is associated with increased tumor cell survival and radioresistance. In this study we explored the efficacy of the novel HSP90 inhibitor AT13387 and examined its radiosensitizing effects in combination with gamma-radiation in 2D and 3D structures as well as mice-xenografts. AT13387 induced effective cytotoxic activity and radiosensitized cancer cells in monolayer and tumor spheroid models, where low drug doses triggered significant synergistic effects on cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 49 publications
(55 reference statements)
7
38
0
Order By: Relevance
“…Indeed, treatment of colorectal cancer cells with NW457 resulted in rapid degradation of ATM and CHK1, two essential upstream kinases of the DNA damage response. This is in accordance with findings of other studies, which showed that targeting HSP90 with small-molecule inhibitors induces the destabilization of different DNA damage response regulators, including ATM, CHK1, DNA-dependent protein kinase (DNA-PK), DNA repair protein RAD51 homologue 1 (RAD51), breast cancer 1 (BRCA1), and others [12, 13, 15, 19, 49, 57, 58]. Importantly, homologous recombination and non-homologous end joining, the two major mechanisms which operate to repair irradiation-induced DNA double strand breaks, appear to be affected to comparable extents [12, 13, 49, 59, 60].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, treatment of colorectal cancer cells with NW457 resulted in rapid degradation of ATM and CHK1, two essential upstream kinases of the DNA damage response. This is in accordance with findings of other studies, which showed that targeting HSP90 with small-molecule inhibitors induces the destabilization of different DNA damage response regulators, including ATM, CHK1, DNA-dependent protein kinase (DNA-PK), DNA repair protein RAD51 homologue 1 (RAD51), breast cancer 1 (BRCA1), and others [12, 13, 15, 19, 49, 57, 58]. Importantly, homologous recombination and non-homologous end joining, the two major mechanisms which operate to repair irradiation-induced DNA double strand breaks, appear to be affected to comparable extents [12, 13, 49, 59, 60].…”
Section: Discussionsupporting
confidence: 92%
“…The anti-tumor efficacy of HSP90 inhibition in combination with radiotherapy has rarely been examined in vivo , and data on HSP90 inhibitor-mediated radiosensitization in colorectal cancer models are scarce [49]. We therefore sought to elucidate the anti-tumor effects of NW457 in combination with radiotherapy in a heterotopic transplantation model of CT26 colorectal cancer cells on Balb/c mice.…”
Section: Resultsmentioning
confidence: 99%
“…Ganetespib, a novel HSP90 inhibitor, exerts its competitive inhibitory effect by binding to the N‐terminal ATP‐binding site, and has been shown to have antitumour activity and lower hepatic and ocular toxicity compared with other HSP90 inhibitors . In addition, HSP90 inhibitors have attracted attention as sensitizers of cancer cells to both conventional chemotherapy and radiation therapy . Therefore, in our study, we investigated the role of HSP90 in the pathogenesis of angiosarcoma and whether the inhibition of HSP90 may have therapeutic potential.…”
mentioning
confidence: 99%
“…The hopes and concerns, about combination therapy with ALK-inhibitors and immunotherapy are pretty the same described with EGFR mutations, with a special interest in adverse events Ongoing but not recruiting [98] 10. …”
Section: Future Perspectives In Alk-rearranged Nsclcmentioning
confidence: 99%